(untitled) (Nepal Journal of Neuroscience, 2026)
Introduction: Intradural tumors are a diverse group of neoplasms that occur within the dural sac, which can be either intramedullary or extramedullary, representing 40% of all spinal tumors. Methods: This was a prospective study conducted at Bir Hospital. 45 patients with intradural spinal tumors who underwent surgical intervention were included. Preoperative neurological status and postoperative neurological outcome were assessed using the Modified McCormick Scale (MMS). Spearman’s correlation test was done for continuous variables and Fisher’s exact/ Kruskal-Wallis test for categorical variables. The change in MMS from pre-operative assessment to the end of follow-up was assessed using Wilcoxon’s signed rank test. P-value <0.05 is considered statistically significant. Results: A total of 45 patients who met the inclusion criteria, with a mean age of 35.9 years, of whom 40 (88.9%) had extramedullary tumors, and 5 (11.1%) had intramedullary tumors. 2 patients presented with cauda equina syndrome. The demographics of patients, like age (p=0.366), sex (p=0.662), and level of tumor (p=0.187), and the surgical approach (Laminectomy vs Laminoplasty) (p=0.126) were not found to be significantly associated with change in MMS, with the strongest predictor being the baseline MMS (p<0.001). However, the location of extramedullary tumors has a better outcome than intramedullary tumors (p<0.003). Conclusion: A good preoperative neurological baseline and location are significant positive predictors of an improved functional outcome. The demographic profile, level of tumor, or surgical approach did not significantly alter the post-operative outcome of patients in our study.